2005
DOI: 10.1021/cm050261d
|View full text |Cite
|
Sign up to set email alerts
|

Second Harmonic Generation of C60Incorporated in Alkali Metal Ion Zeolites and Mesoporous MCM-41 Silica

Abstract: Different loadings of C60 have been incorporated in mesoporous MCM-41 aluminosilicate as well as proton and alkali metal ion zeolites. These samples show non-linear optics activity whose efficiency increases upon C60 content, size of the alkali metal ion, and laser exposure. The later unprecedented second harmonic generation (SHG) enhancement effect can lead up to 2 orders of magnitude efficiency increase. After having irradiated the solid, the SHG enhancement decays upon standing in the dark toward the initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…Herance et al showed that the efficiency of guest molecules to generate SHG depends on the pore dimensionality of the interconnected pore system as follows: 1D > 2D > 3D [24]. A few studies have reported the SHG-activity of host/guest assemblies in which the host structure is mesoporous silica [78][79][80]. Typically the guest species are rather large [78,79], and in one instance the SHG-active chromophore was covalently attached to the silica walls during synthesis of the porous material [79].…”
Section: Zeolites As Nlo Materialsmentioning
confidence: 99%
“…Herance et al showed that the efficiency of guest molecules to generate SHG depends on the pore dimensionality of the interconnected pore system as follows: 1D > 2D > 3D [24]. A few studies have reported the SHG-activity of host/guest assemblies in which the host structure is mesoporous silica [78][79][80]. Typically the guest species are rather large [78,79], and in one instance the SHG-active chromophore was covalently attached to the silica walls during synthesis of the porous material [79].…”
Section: Zeolites As Nlo Materialsmentioning
confidence: 99%
“…20 Due to their channel structure, ion-exchange properties, and molecular and size recognition, many ions and molecules have been immobilized within zeolites channels. [21][22][23][24][25][26] MCM-41 is also a silicate material such as zeolites, but with larger pores and a less crystalline structure. In this work we report how to efficiently cover the external surface of silicates (Zeolite-Y and MCM-41) with different pore sizes, framework structures and aluminum content with SWCNTs (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Fullerene-based materials exhibit interesting characteristics such as photovoltaic responses, superconductivity upon doping with alkali metals, nonlinear optical properties, and biological activity . Furthermore, fullerenes have frequently been used as an efficient electron acceptor component in D−A linked molecules .…”
Section: Introductionmentioning
confidence: 99%